Entre la parodie et l'imitation: le Don Juan de Jacques Ferron - Mercier, Andrée (Romanica Silesiana)
The article analyzes conceptual links between the play “Le Don Juan chretien“ by Jacques Ferron and its original version by Moliere. The author shows how the myth of Don Juan as a seducer paves the way for the modification of the role of the woman, by means of redefining her social status. The assumption of the article is that Ferron’s play becomes a part of the literary tradition of Quebec, by building on its cultural and linguistic heritage. Key-words: Jacques Ferron; intertextuality; parody; imitation; the myth of Don Juan